2019
DOI: 10.1186/s40795-019-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lunch provision on anthropometry, hemoglobin, and micronutrient status of female Cambodian garment workers: exploratory randomized controlled trial

Abstract: Background: Lunch provision is expected to improve the nutritional status of Cambodian garment workers. The objective of this study is to evaluate the effects of a model lunch provision through a canteen on anthropometry, hemoglobin, and micronutrient status in female garment workers in Cambodia. Methods: This exploratory randomized controlled trial was implemented at a garment factory in Phnom Penh, Cambodia. Female workers (nulliparous, non-pregnant) were recruited and randomly allocated into an intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Twenty‐five studies 12,16,30–32,35,36,51,52,55–57,59,62–65,67–69,79,80,89,91,93 reported improvements in nutrition outcomes from baseline to post‐intervention or compared to a control. One study 38 indicated negative findings, four showed no significant changes 15,34,37,53 and nine had mixed findings 11,13,58,66,69,70,97–99 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐five studies 12,16,30–32,35,36,51,52,55–57,59,62–65,67–69,79,80,89,91,93 reported improvements in nutrition outcomes from baseline to post‐intervention or compared to a control. One study 38 indicated negative findings, four showed no significant changes 15,34,37,53 and nine had mixed findings 11,13,58,66,69,70,97–99 …”
Section: Resultsmentioning
confidence: 99%
“…One study 38 indicated negative findings, four showed no significant changes 15,34,37,53 and nine had mixed findings. 11,13,58,66,69,70,[97][98][99] Two-thirds of interventions (n = 67) measured compliance, such as recording leftovers, identifying consumption in DA methods, record of attendance or direct questions in survey.…”
Section: Nutrition Intervention Studiesmentioning
confidence: 99%